Пошаговое объяснение:
(3х - 1)² - 8(х + 1)² = (х + 2)(х - 2)
(9х² - 6х + 1) - 8(х² + 2х + 1) = х² - 2х + 2х - 4
9х² - 6х + 1 - 8х² - 16х - 8 = х² - 4
х² - 22х - 7 = х² - 4
-22х - 7 = -4
-22х = -4 + 7
-22х = 3
х = 3 : (-22)
х = -3/22
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
(3х - 1)² - 8(х + 1)² = (х + 2)(х - 2)
(9х² - 6х + 1) - 8(х² + 2х + 1) = х² - 2х + 2х - 4
9х² - 6х + 1 - 8х² - 16х - 8 = х² - 4
х² - 22х - 7 = х² - 4
-22х - 7 = -4
-22х = -4 + 7
-22х = 3
х = 3 : (-22)
х = -3/22